PENGARUH PENEMPATAN PERAWAT DAN INSENTIF TERHADAP KINERJA PERAWAT PADA RSIA ERIA BUNDA PEKANBARU - Ulfa Anjelita; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of nurse placement and incentive partially and simultaneously. This study used a questionnaire as a tool for gathering data distributed to 94 respondents to nurses at RSIA Eria Bunda Pekanbaru. The data is then processed using descriptive analysis and statistical analysis using SPSS 24.0 by conducting validity, reliability testing, simple linear regression analysis, multiple linear analysis, determination analysis (R2) and hypothesis testing with t test (partial test) and F test (simultaneous).The result showed that the first hypothesis testing is nurses placement on nurses performance, namely tarithmetic (9,704) > ttable (1,986), meaning that nurses placement has a significant effect on nurses perfoemance. The second incentive is tarithmetic (12,886) > ttable (1,986), meaning that incentive has a significant effect on nurses performance. Test result Farithmetic (92,843) > Ftable, (3,100) meaning that nurses placement and incentive simultaneously have a significant effect on nurses performance.  Keywords: Nurses Placement, Incentive, Nurses Performance